2021
DOI: 10.1097/corr.0000000000001610
|View full text |Cite
|
Sign up to set email alerts
|

Can the Femoro-Epiphyseal Acetabular Roof (FEAR) Index Be Used to Distinguish Dysplasia from Impingement?

Abstract: Background Classifying hips with structural deformity on the spectrum from impingement to dysplasia is often subjective and frequently inexact. Currently used radiographic measures may inaccurately predict a hip’s morphological stability in borderline hips. A recently described radiographic measure, the Femoro-Epiphyseal Acetabular Roof (FEAR) index, has demonstrated an ability to predict stability in the borderline hip. This measure is attractive to clinicians because procedures can be used on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…FEAR index and acetabular anteversion have been shown to be greater in patients with dysplasia compared with patients with femoroacetabular impingement (FAI) without dysplasia. 19,20 FEAR index is intended to predict hip stability based on the concept that the physis is oriented perpendicular to the joint reactive forces during growth. 15 Positive measurements indicate that joint reactive forces favor lateral migration of the femoral head and instability (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FEAR index and acetabular anteversion have been shown to be greater in patients with dysplasia compared with patients with femoroacetabular impingement (FAI) without dysplasia. 19,20 FEAR index is intended to predict hip stability based on the concept that the physis is oriented perpendicular to the joint reactive forces during growth. 15 Positive measurements indicate that joint reactive forces favor lateral migration of the femoral head and instability (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…While there were no statistically significant differences for any radiographic measurements between cohorts, there was a trend towards a significantly greater FEAR index (1.3±8.0 vs. −2.1±9.0, P =0.144), AV3 (21.4±7.0 vs. 19.1±5.2, P =0.137), and alpha angle (59.8±8.4 vs. 56.5±8.8, P =0.156) measurements in the infantile DDH treatment cohort. FEAR index and acetabular anteversion have been shown to be greater in patients with dysplasia compared with patients with femoroacetabular impingement (FAI) without dysplasia 19,20. FEAR index is intended to predict hip stability based on the concept that the physis is oriented perpendicular to the joint reactive forces during growth 15.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies looking at the FEAR index found it to be a predictor of patients undergoing osteotomy for hip instability/dysplasia and of patients with a diagnosis of microinstability at the time of hip arthroscopy. 25,26,30 An ACEA of \17°is another radiographic marker that is associated with a worse outcome after hip arthroscopy in patients with borderline dysplasia, as determined by their LCEA. 8 The AWI, similar to the ACEA, is a measure of anterior coverage of the acetabulum.…”
Section: Discussionmentioning
confidence: 99%
“…Differentiating between FAI and mild/borderline dysplasia is notoriously difficult, both radiographically and clinically. 3 This challenge can lead to suboptimal outcomes through delayed treatment or treatment of the wrong presumptive diagnosis. 3 Techniques are still being developed to distinguish between patients with impingement and mild or borderline dysplasia, such as the femoral epiphysis acetabular roof (FEAR) index.…”
mentioning
confidence: 99%
“…3 Techniques are still being developed to distinguish between patients with impingement and mild or borderline dysplasia, such as the femoral epiphysis acetabular roof (FEAR) index. 3…”
mentioning
confidence: 99%